Response of choroidal blood flow to carbogen breathing in smokers and non-smokers. Issue 6 (17th May 2004) - Wimpissinger, B; Resch, H; Berisha, F; Weigert, G; Schmetterer, L; Polak, K
Abstract : Aim: To investigate a potential difference in ocular vascular reactivity during carbogen breathing in optic nerve head, choroid, and retina between healthy smokers and non-smokers. Methods: 25 (13 smokers and 12 non-smokers) healthy male volunteers participated in this observer masked, two cohort study. During inhalation of carbogen (5% CO2 and 95% O2 ) over 10 minutes measurements were taken using laser Doppler flowmetry to assess submacular choroidal and optic nerve head blood flow, laser interferometry to assess fundus pulsation amplitudes, and retinal vessel analyser (RVA) to assess retinal vessel diameters. Results: At baseline choroidal blood flow was higher (p = 0.018, ANOVA) in smokers than in non-smokers. During administration of carbogen the response in choroidal blood flow was significantly different between the two groups: there was an increase in non-smokers after carbogen breathing (p = 0.048) compared with relatively stable blood flow in smokers (p = 0.049 between groups, ANOVA). A similar response pattern was seen for fundus pulsation amplitude, which increased notably after carbogen breathing in non-smokers but not in smokers (p<0.001 between groups, ANOVA). Optic nerve head blood flow and retinal vessel diameters were reduced in both groups to a comparable degree during carbogen breathing. Conclusion: The study indicated abnormal choroidal vascular reactivity in chronic smokers. These early haemodynamic changes may be related to the increased risk to smokers of developing ocular vascular diseases. The specific mechanisms underlying abnormal choroidal vascular reactivity in chronic smokers remain to be characterised.